Fractal Dimension of a Random Invariant Set and Applications. (7th November 2013) - Wang, Gang; Tang, Yanbin
Abstract : We prove an abstract result on random invariant sets of finite fractal dimension. Then this result is applied to a stochastic semilinear degenerate parabolic equation and an upper bound is obtained for the random attractors of fractal dimension.